Предмет: Алгебра,
автор: xtywjdf
( а+1 )( а+2)( а²+4)(а²+1)(а-2)(а-1) преобразовать в многочлен
Ответы
Автор ответа:
0
(a+1)(a+2)(a²+4)(a²+1)(a-2)(a-1)
(a+1)(a-1) = (a²-1)
(a²+1)(a²-1) = (a⁴-1)
(a+2)(a-2) = (a²-4)
(a²+4)(a²-4) = (a⁴-16)
(a⁴-1)(a⁴-16) = a⁸-16a⁴-a⁴+16 = a⁸-17a⁴+16
(a+1)(a-1) = (a²-1)
(a²+1)(a²-1) = (a⁴-1)
(a+2)(a-2) = (a²-4)
(a²+4)(a²-4) = (a⁴-16)
(a⁴-1)(a⁴-16) = a⁸-16a⁴-a⁴+16 = a⁸-17a⁴+16
Автор ответа:
0
всё по формуле a^2-b^2 = (a-b)(a+b)
Похожие вопросы
Предмет: Русский язык,
автор: aydin20097768
Предмет: Математика,
автор: devochka5972
Предмет: Русский язык,
автор: Аноним
Предмет: Информатика,
автор: yulia1335
Предмет: Математика,
автор: ПУПСОЙД